2016
DOI: 10.1074/jbc.m115.693580
|View full text |Cite
|
Sign up to set email alerts
|

O-Linked β-N-acetylglucosamine (O-GlcNAc) Acts as a Glucose Sensor to Epigenetically Regulate the Insulin Gene in Pancreatic Beta Cells

Abstract: The post-translational protein modification O-linked ␤-Nacetylglucosamine (O-GlcNAc) is a proposed nutrient sensor that has been shown to regulate multiple biological pathways. This dynamic and inducible enzymatic modification to intracellular proteins utilizes the end product of the nutrient sensing hexosamine biosynthetic pathway, UDP-GlcNAc, as its substrate donor. Type II diabetic patients have elevated O-GlcNAc-modified proteins within pancreatic beta cells due to chronic hyperglycemia-induced glucose ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 76 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…The same idea can also be invoked to explain O-GlcNAcylation functions in type 2 diabetes (35), thus reframing both disease phenotypes as a defect in pol II elongation genome-wide. Indeed, increased O-GlcNAcylation and glucose flux resulted in increased expression of a subset of genes in beta cells of the pancreas (70).…”
Section: Polmentioning
confidence: 99%
“…The same idea can also be invoked to explain O-GlcNAcylation functions in type 2 diabetes (35), thus reframing both disease phenotypes as a defect in pol II elongation genome-wide. Indeed, increased O-GlcNAcylation and glucose flux resulted in increased expression of a subset of genes in beta cells of the pancreas (70).…”
Section: Polmentioning
confidence: 99%
“…Like phosphorylation, O -GlcNAcylation is a reversible modification that affects the function of target proteins. OGT’s targets regulate gene expression [18,19], metabolism [16,20,21], and signaling [22,23], consistent with OGT’s role in development and disease [24,25].…”
Section: Introductionmentioning
confidence: 83%
“…Recently, O -GlcNAc has emerged as an epigenetic regulator of gene expression through its influence on higher-order chromatin structure, transcription and modulation of RNA polymerase II. 80 , 81 Thus, it is suggested that O -GlcNAcylation might link hyperglycemia to epigenetic. 81 , 82 Indeed, growing evidences have demonstrated that prolonged exposure to HG epigenetically affects gene expression to the level that alterations remain stable in the absence of hyperglycemia, an effect known as Hyperglycemic memory.…”
Section: Discussionmentioning
confidence: 99%